Competition and Strategic Information Acquisition in Credit Markets - Hauswald, Robert; Marquez, Robert (Review of Financial Studies, 2006)
We investigate the interaction between banks' use of information acquisition as a strategic tool and their role in promoting the efficiency of credit markets when a bank's ability to gather information varies with its distance to the borrower. We show that banks acquire proprietary information both to soften lending competition and to extend their market share. As competition increases, investments in information acquisition fall, leading to lower interest rates but also to less efficient lending decisions. Consistent with the recent wave of bank acquisitions, we also find that merging for informational reasons with a competitor is an optimal response to industry consolidation.